Prevalence and risk factors of dengue and chikungunya infections among febrile children at Busia County Referral Hospital in western Kenya - Ambogo, I.N. (2016)
Background: Fever is the largest cause of child morbidity and mortality in Africa. Dengue and Chikungunya infections have been identified among commonly undiagnosed viral etiologies of fever even in malaria endemic areas. Objectives: To determine the prevalence and risk factors of Dengue and Chikungunya infections and estimate coinfection with malaria among children aged 1- 12 years presenting with fever at Busia County Referral Hospital. Methods: We conducted a cross sectional hospital based study where we recruited randomly selected children presenting with fever. Questionnaires were administered and venous blood samples collected and tested by microscopy and PCR. Means and medians were calculated for continuous data and proportions for categorical data. Chi square test was performed for difference in proportions and multivariate logistic regression was used to determine independent associations at 95% confidence level. Results: Of the 396 febrile children enrolled, 203 (51.3%) were males, 309 (78.0%) were aged below 5 years and 264 (66.7%) resided in Matayos Sub-County. The median duration of illness was 2 days (IQR 1.5) and the commonest symptom was vomiting in 145 (36.6%) of the children. A total of 21 (5.3%) children were confirmed to have chikungunya of which 2 (9.5%) were co-infected with malaria. None of the children tested was confirmed to have dengue. Positive malaria microscopy (aOR 0.18, CI 0.05-0.66) and joint pain (aOR 3.68-18.89) were found to be independently associated with chikungunya infection. Conclusions: Mainly chikungunya virus appears to be actively circulating in Western Kenya even in the absence of a declared outbreak. Recommendations: We recommend establishment of prevention measures and laboratory testing of febrile cases for chikungunya in these areas.